Optical Spectroscopy and Computational Methods in Biology and Medicine - Baranska, Malgorzata (Challenges and Advances in Computational Chemistry and Physics, 2014)
This multi-author contributed volume gives a comprehensive overview of recent progress in various vibrational spectroscopic techniques and chemometric methods and their applications in chemistry, biology and medicine. In order to meet the needs of readers, the book focuses on recent advances in technical development and potential exploitations of the theory, as well as the new applications of vibrational methods to problems of recent general interest that were difficult or even impossible to achieve in the not so distant past.    Integrating vibrational spectroscopy and computational approaches serves as a handbook for people performing vibrational spectroscopy followed by chemometric analysis hence both experimental methods as well as procedures of recommended analysis are described. This volume is written for individuals who develop new methodologies and extend these applications to new realms of chemical and medicinal interest.